Laboratory evaluation of a novel anaesthesia delivery device. (26th October 2016) - Paul, A.; Clark, J. N.; Salama, I. E.; Jenkins, B. J.; Goodwin, N.; Wilkes, A. R.; Mahoney, P. F.; Hall, J. E.
Summary: Here, we describe proof of concept of a novel method for delivering volatile anaesthetics, where the liquid anaesthetic (sevoflurane or isoflurane) is formulated into an emulsion that is contained in a compact, lightweight device through which carrier gas flows. Release of anaesthetic is achieved by stirring of the formulation, allowing controlled and responsive release of anaesthetic at a variety of fixed flow rates between 0.5 l.min −1 and 5 l.min −1, with ventilated, non‐ventilated and draw‐over breathing systems. Anaesthetic release was evaluated using target anaesthetic concentrations ranging from 0.5% v/v to 8% v/v to mimic those typically required for induction and maintenance of anaesthesia, and lower concentrations suitable for sedation. Under all conditions, output could be maintained within 0.1% v/v of the intended setting, and the device could deliver a controlled level of anaesthetic for at least 60 min, with compensation for different ambient temperatures (10–30 °C) and carrier gas flow rates. This device offers a simple, inexpensive method of delivering safe concentrations of volatile anaesthetics for a wide range of applications.